On-farm conservation of neglected and underutilised species - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
The project ‘Reinforcing the resilience of poor rural communities in the face of food insecurity, poverty and climate change through on-farm conservation of local agrobiodiversity’ will: investigate the use of neglected and underutilized species in increasing the adaptation and resilience of production systems in the face of climate change; examine the role of men and women farmers in conservation practices; develop participatory monitoring systems for local agrobiodiversity; and strengthen on farm conservation and the role of custodian farmers.